KAJIAN KINERJA ANGKUTAN UMUM (MIKROLET) DI KOTA KENDARI - Alfian Ishak (Yayasan Akrab Pekanbaru, 2019)
Public transportation (minibus) in Kendari Town often mentioned as one cause of congestion on some roads line in town because vehicle proportion of road users for public transportation routes dominated by minibus, while on other routes, the amount of minibus particularly at peak hours is too less. This study aimed to determine the performance of public transportation (minibus) in Kendari Town, by observing and analyzing some characteristics of accessibility, existing conditions, waiting time (headway) and passenger capacity (load factor) of public transportation. The research results showed that the optimal fleet size to 3 observation routes namely 818 units of vehicles, not increase continuously, so needed continuous licensing rules that are strictly enforced and established according to the needs of passengers. The government should divert the fleet operating in excess fleet route to other routes are still needed. Headway the standards required, in order to avoid accumulation of vehicles on certain roads impassable, by allocation another route or a new route for the majority of public transport in operation, to prevent or reduce the occurrence of seizure that resulted in passenger traffic and public transportation chaos.